Kualitas Pelayanan Publik di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Boalemo - Kamumu, Rahmat Raihan; Aneta, Asna; Aneta, Yanti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
quality values in the Boalemo Regency Population and Civil Registration Service through the dimensions (1) Tangible, (2) Reliability, (3) Responsiveness, (4) Assurance, (5) Empathy. The research method used is qualitative with descriptive research type. Data collection was carried out by observation, interviews and documentation. The results of this research show that the implementation of public service quality values in the Boalemo Regency Dukcapil Disdukcapil has been carried out well and is in accordance with the provisions of Law Number 25 of 2009 concerning public services. In terms of dimension (1) Tangible, it is in accordance with the service standards set to provide satisfaction to the community served, however, the attitudes and behavior of employees in providing services to vulnerable communities must be given more attention. (2) Reliability, employee attitudes and behavior in confirming service procedures are in accordance with both technical and administrative requirements that are easy to understand and implement. (3) Responsiveness, the completion time for types of services still needs to be adjusted so that the targets to be achieved are more effective and efficient. (4) Assurance, service fees are in accordance with Law Number 25 of 2009 where there are no fees charged to the public. (5) Empathy, is good enough to understand the desires and needs to satisfy the community as service recipients.